P-771 Subfertility versus in vitro fertilization procedures: unravelling the origins of fetal cardiac remodeling in assisted reproductive technologies. (30th June 2022) - Boutet, M.L; Casals, G; Valenzuela-Alcaraz, B; García-Otero, L; Crovetto, F; Carrillo, P; Borrás, A; Cívico, M.S; Manau, D; Gratacós, E; Crispi, F
Abstract: Study question: Do spontaneously conceived (SC) fetuses from subfertile couples present signs of cardiac remodeling as those observed after in vitro fertilization (IVF) treatments? Summary answer: SC fetuses from subfertile couples do not associate cardiac remodeling, and their cardiac structure and function are similar to those of SC from fertile couples. What is known already: Fetuses and children from IVF associate cardiac remodeling and suboptimal function, including dilated atria, more globular and thicker ventricles, reduced longitudinal motion and impaired relaxation in utero and after birth. Fetal cardiac changes have been demonstrated both after fresh and frozen embryo transfer. The SC fetuses used as 'controls' in our previous publications were conceived by fertile couples thus making it difficult to separate the contribution of infertility per se from the IVF procedures on cardiac programming. There are no previous cardiovascular studies investigating the independent effects of infertility in SC fetuses from subfertile couples (time-to-pregnancy (TTP) over 12 months). Study design, size, duration: Prospective cohort study of 289 singleton pregnancies recruited from 2017 to 2021, including 96 SC pregnancies from fertile couples (TTP less than 12 months), 97 SC from subfertile couples (TTP over 12 months) and 96 from IVF after fresh ET. Fetal echocardiography was performed in all pregnancies. Epidemiological data and perinatal outcomes were collected in all pregnancies. Participants/materials, setting, methods: IVF pregnancies from our centre were identified as eligible at pregnancy diagnosis. Eligible SC pregnancies from fertile and subfertile couples who attended our Maternal-Fetal Unit were invited to participate at third trimester, being matched to the IVF pregnancies by maternal age. Fetal echocardiography was performed at 29-34 weeks of pregnancy to assess cardiac structure and function. Echocardiographic comparisons were adjusted by nulliparity, birthweight centile, gestational age and estimated fetal weight at scan. Main results and the role of chance: Parental age, ethnicity, body mass index and smoking exposure, median gestational age and estimated fetal weight were similar in all study groups. There were no significant differences in infertility duration or aetiology between the subfertile and the IVF populations (TTP: subfertile median 30 months [IQR 20-54] versus IVF: 47 [25-61]; p-value=0.052). While both fertile and subfertile SC groups presented similar fetal cardiac results, IVF fetuses showed larger atria (right atria-to-heart ratio: IVF mean 18.9% [SD 3.4] versus subfertile 17.8% [3.5] versus fertile 17.6% [3.3]; adjusted P-value<0.001), more globular ventricles (right ventricular sphericity index: IVF 1.56 [0.25] versus subfertile 1.72 [0.26] versus fertile 1.72 [0.26]; <0.001), and thicker myocardial walls (relative wall thickness: IVF 0.86 [0.22] versus subfertile 0.64 [0.13] versus fertile 0.64 [0.18]; <0.001). Whereas SC fetuses from fertile and subfertile couples had preserved cardiac function, IVF fetuses showed signs of suboptimal systolic and diastolic function with reduced tricuspid ring displacement (IVF 7.26 mm [1.07] versus subfertile 8.04 mm [1.18] versus fertile 7.89 mm [1.51]; <0.001) and increased left myocardial performance index (IVF 0.49 [0.08] versus subfertile 0.45 [0.09] versus fertile 0.45 [0.10]; <0.001). A sub-analysis including only unexplained infertility cases in subfertile SC and IVF groups showed similar results. Limitations, reasons for caution: The fetal cardiac changes reported here are subclinical, with most cardiovascular parameters lying within normal ranges. Although echocardiographic changes are recognized as potential cardiovascular risk factors, their association with long-term cardiovascular disease remains to be proven. Wider implications of the findings: Subfertility per se does not seem to be associated to fetal cardiac remodeling, which have been previously described in IVF fetuses. Future studies are warranted to further investigate the factors related to fetal cardiac changes associated to ART. Trial registration number: Not a trial